2017
DOI: 10.1021/acscatal.7b02203
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative Strategies for Catalytic Hydrogenation of Unsaturated Hydrocarbons

Abstract: This Perspective discusses catalytic hydrogenation reactions of alkenes, alkynes, and other unsaturated C−C substrates in which the catalyst design involves cooperative strategies that enable bifunctional H 2 activation and delivery. These approaches complement the more traditional use of single-site precious metal systems for such hydrogenation reactions in homogeneous catalysis. Strategies included in this Perspective are cooperation between (a) a catalytic metal site and a basic ligand residue, (b) a cataly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(43 citation statements)
references
References 92 publications
1
42
0
Order By: Relevance
“…MLC via ligands that feature a Lewis acid moiety is still an emerging area of (de)hydrogenation catalysis. 16 The importance of MLC pathways in stoichiometric (de)hydrogenation studies has been demonstrated frequently, [17][18][19][20][21] but this can be difficult to translate to catalytic regimes which are extremely challenging to study experimentally. Much of the…”
Section: Metal-ligand Cooperativitymentioning
confidence: 99%
See 1 more Smart Citation
“…MLC via ligands that feature a Lewis acid moiety is still an emerging area of (de)hydrogenation catalysis. 16 The importance of MLC pathways in stoichiometric (de)hydrogenation studies has been demonstrated frequently, [17][18][19][20][21] but this can be difficult to translate to catalytic regimes which are extremely challenging to study experimentally. Much of the…”
Section: Metal-ligand Cooperativitymentioning
confidence: 99%
“…Within the realm of cooperative (de)hydrogenation catalysis, MLC systems are at the forefront, whereas MMC systems are relatively scarce. 6,9,16 This provides an opportunity to compare and contrast these two modes of cooperativity. As seen above, MLC strategies rely heavily on the presence of complementary acidic (e.g.…”
Section: Metal-metal Cooperativitymentioning
confidence: 99%
“…Incorporation of LA moieties into ligand frameworks has garnered interest for catalytic applications,where the LA can be another TM, [5] am ain group metal, [6] or lanthanide ion. [7] Ty pically,main group LAs act as s-acceptor ligands,engaging the TM in an inverse dative bond, or Z-type interaction.…”
Section: Introductionmentioning
confidence: 99%
“…The interest in homobimetallic catalysts has recently seen a renaissance 6. Selected catalytic applications include diazo-free cyclopropanation,7 small molecule activation,8,9 hydrogenation,10 hydroformylation11 and C–C coupling reactions 12. Notably, heterobimetallic complexes serve as models of the transmetallation step for the latter process 13–17.…”
Section: Introductionmentioning
confidence: 99%